Performance measurement of essential public health functions in three municipalities, Antioquia-Colombia, 2011 - Blanca M. Chávez G; Alejandra M. Arango A; Ana M. Zuleta G (Universidad de Antioquia, 2011)
Objective: to measure the performance of the Essential Public Health Functions (ephf) in three municipalities from the Penderisco area of Southwestern Antioquia (a zone encompassing three municipalities: Betulia, Concordia, and Salgar) in 2011. Methodology: we conducted a cross-sectional descriptive study in three municipalities. To this end, we adapted the instrument for measuring ephf for use in Colombia. The instrument was developed by the paho, and we implemented its adapted version locally. The instrument was adjusted to the skills and fields of action of the municipal authorities, the questions that were not relevant for the local context were removed, and the formulas for generating scores and indicators were re-calculated. The instrument was applied to a group of experts in each municipality. Results: in the Penderisco zone, three functions had optimal performance: ephf1, ephf4, ephf2. Additionally, the functions labeled ephf3, ephf5, ephf6, ephf7, ephf8, ephf9, and ephf11 had above average performance. ephf10, in turn, showed minimum perfor- mance. Two indicators of development of capacity and infrastructure for public health were classified as weaknesses, namely: knowledge, skills, and mechanisms to review, refine and enforce the regulatory framework and development of institutional research capacity. This is consistent in the three municipalities. Conclusions: In spite of the efforts made by countries to improve the performance of the essential public health functions, development is still budding; the same scenario is seen in the studied municipalities. Few functions had optimal performance and were considered strengths and capacity development and the infrastructure for supporting the development of essential public health functions are weak.